Biometric Fingerprint Systems for Secure and Efficient Attendance Tracking in Workplaces and Universities - Tanmeet Kaur; Ashutosh Pratap Singh; Anshul Nagar; Sumit Kumar Singh (International Journal of VLSI Circuit Design & Technology, 2024)
A fingerprint attendance system, which uses each person's unique fingerprint rather than more conventional techniques like sign-in sheets or ID cards, is a simple and dependable approach to keeping track of who is present. The device instantly compares the user's finger to the fingerprint on file when they place it on a scanner, thereby recording their attendance. This avoids errors such as someone signing in on behalf of others or failing to record attendance. Attendance is immediately recorded and readily tracked because the system operates in real time. It helps increase productivity in workplaces, schools, and other settings by making attendance tracking safer, quicker, and more accurate overall. The installation of a fingerprint-based attendance management system in a university setting is the main goal of this study to overcome the difficulties associated with managing student attendance during lecture periods. The system uses fingerprints, a biometric identification method that is unique and consistent throughout an individual's life, to address the issue of impersonation and ghost workers in the public and private sectors. One of the system's unique abstractions is its use in a university setting, where it solves the problem of student attendance tracking, which is essential for a successful assessment of academic performance.
Keywords: Fingerprint; authentication; crossing number; enrollment; minutiae score attendance management